A Model for Improving the Performance of Regional Councils in the Province of South Sumatra in the Delivery and Absorption of Public Aspirations - Kiemas, Giri Ramanda; Sobri, Kgs. M.; Lionardo, Andries; Putra, Raniasa (Journal of Posthumanism, 2025)
The purpose of this research is to answer measurably and scientifically, so this research has the following objectives. 1. To identify the performance of local councils in South Sumatra Province in delivering and absorbing public aspirations. 2. To identify the factors that influence the performance of local councils in South Sumatra Province in delivering and absorbing public aspirations. 3. To identify the ideal model to be used in implementing the performance of local councils in South Sumatra Province in delivering and absorbing public aspirations. The method used in this research was the descriptive qualitative method. This research reviewed concepts and collected facts. Furthermore, this research intends to describe and explain the Performance Improvement Model of DPRDs in South Sumatra Province in the Absorption and Delivery of Public Aspirations. Knowing the performance of DPRDs in South Sumatra Province in the delivery and absorption of public aspirations. To identify the factors that will influence the performance of DPRDs in South Sumatra Province in delivering and absorbing public aspirations. Knowing the ideal model to be used in implementing the performance of DPRDs in South Sumatra Province in delivering and absorbing public aspirations. Improving the performance of local councils in South Sumatra Province in delivering and absorbing public aspirations through the assessment of New Public Service theory and the Measurement Model of Local Council Performance Accountability in the Context of Good Governance towards excellent service or Good Government.